Public Budget Efficiency Strategy in the Regions: Between Transparency, Innovation, and Public Participation: JEL Classification: H61; H72; H77; H83; D73 - Mahyudin Mahyudin; Sry Mayunita; Junaid Gazalin (Newinera Publisher, 2026)
This study examines strategies for public budget efficiency in Buton Regency, Southeast Sulawesi Province, focusing on three key aspects: transparency, innovation, and public participation. The findings indicate that budget efficiency is not only determined by the government’s ability to cut costs but also by the quality of participatory and transparent governance. First, the current condition of Buton shows that a large portion of the regional budget is absorbed by personnel expenditure, with several programs still misaligned with community needs. Second, transparency serves as the foundation of efficiency, reflected in the improvement of the regional information disclosure index, although consistency in data publication remains a challenge. Third, public service innovation through the Public Service Mall (MPP) has successfully reduced average service time from six days to two days, while lowering operational costs and increasing citizen satisfaction. Fourth, public participation through the Musrenbang forums is relatively high, yet digital oversight and the role of civil society organizations remain limited. Thus, strategies for public budget efficiency at the regional level should integrate strong transparency, community-oriented service innovation, and inclusive public participation to achieve efficient, accountable, and equitable local governance.